Child and Adolescent Psychiatric Inpatient Care: Contemporary Practices and Introduction of the 5S Model. Issue 4 (2nd October 2022) - Calhoun, Casey D.; Nick, Elizabeth A.; Gurtovenko, Kyrill; Vaughn, Aaron J.; Simmons, Shannon W.; Taylor, Rebecca; Twohy, Eileen; Flannery, Jessica; Thompson, Alysha D.
ABSTRACT: Children and adolescents admitted to psychiatric inpatient units typically present with severe psychopathology, trauma histories, and risk to self or others. Unfortunately, inpatient care has proven to be largely ineffective in changing the course of mental illness for these youth, with many experiencing readmission or continued risk following discharge. A critical examination of child and adolescent psychiatric inpatient practices, and guiding models of care, are greatly needed. This comprehensive review provides an overview of contemporary inpatient care, highlighting specific areas where empirically-informed guidance is present and lacking. The content reviewed includes: scope and structure of inpatient care, intake and evaluation, safety and security, therapeutic interventions, and discharge planning. Following our review, we present the 5S model as a guiding framework for inpatient care and continued research. Lastly, given the critical importance of inpatient care and the sparse empirical literature in this area, we issue a call for research investigating all aspects of inpatient care from admission to post-discharge.